2010
DOI: 10.14411/eje.2010.072
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the genus Phonochorion (Orthoptera: Tettigoniidae: Phaneropterinae)

Abstract: Abstract. Phonochorion Uvarov (Orthoptera: Tettigoniidae: Phaneropterinae) is a little known genus consisting of three species: Ph. satunini, Ph. artvinensis and Ph. uvarovi. The objective of this study is to conduct a thorough distributional, taxonomic and systematic revision of the genus Phonochorion using both bioacustic and external morphological characters. Field surveys indicate that the genus is distributed from the Trabzon region of Turkey to the Khulo province of Georgia however the exact limit of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…Only males producing calling songs were used in mating trials. The typical calling songs of both species are different (Sevgili et al 2010). In preliminary studies, it was found that the females were not sexually receptive until 7 days after adult eclosion.…”
Section: Mating Experimentsmentioning
confidence: 96%
See 4 more Smart Citations
“…Only males producing calling songs were used in mating trials. The typical calling songs of both species are different (Sevgili et al 2010). In preliminary studies, it was found that the females were not sexually receptive until 7 days after adult eclosion.…”
Section: Mating Experimentsmentioning
confidence: 96%
“…The genus Phonochorion Uvarov, 1916 (Orthoptera: Phaneropterinae) is a small genus consisting of three species: P. satunini, P. artvinensis and P. uvarovi (Sevgili et al 2010). These species are distributed only on the northern slopes of the East Black Sea of Turkey and Lesser Caucasus Mountains in Georgia.…”
Section: The Insectsmentioning
confidence: 99%
See 3 more Smart Citations